Poulantzas e o direito - Luiz Eduardo Motta (Universidade do Estado do Rio de Janeiro, 2010)
The aim of this article is to reclaim the analysis by Nicos Poulantzas on the problem of the law and thereby discuss the changes in his political theory over time. To discuss the changes in the concept of law in Poulantzas' political theory, the article is divided into three parts: 1) a focus on his existential-Marxist phase, in which the principal reference is his work Nature des Choses et du Droit; 2) Althusser's strong influence on his theory, as exemplified primarily by Political Power and Social Classes; and 3) the influence of both Poulantzas' work and the critique thereof on Foucault's theory of power, marking the last phase of his career and concluding with State, Power, Socialism.